A comparative study of the reproduction, autecology and genetic diversity of Brachysiphon rupestris, B. acutus and some other species of the Penaeaceae - Louw, N.(Nicolette) (Stellenbosch : Stellenbosch University, 2012)
Dissertation (Ph. D.) -- University of Stellenbosch, 1996.